Phytochemical analysis and antiproliferative activity of the aerial parts of Scrophularia subaphylla - Abbas Delazar; Solmaz Asnaashari; Elhameh Nikkhah; Parina Asgharian (Wolters Kluwer Medknow Publications, 2019)
Scrophularia subaphylla (S. subaphylla) L., a medicinal plant from the Scrophulariaceae family, has been reported to possess potential profits in the treatment and prophylaxis of different diseases. Some phenolic compounds in this genus have been displayed decent effects on different types of cancer via multiple mechanisms. The current study aimed to bioassay guided isolation of cytotoxic constituents from the aerial parts of S. subaphylla against breast (MCF-7) and colon (HT-29) cancer cell lines as well as normal cells (L929). Different extracts of S. subaphylla were acquired by Soxhlet apparatus and then subjected to brine shrimp lethality test and MTT assay for assessing their cytotoxic characteristics. Cytotoxic extract subjected to further phytochemical fractionation using solid phase extraction, reversed-phase high pressure liquid chromatography (RP-HPLC), and one dimensional nuclear magnetic resonance (1D-NMR) spectroscopy. The biological activity of the isolated pure components, verbascoside and 3´ O rhamnosyl -4´ O para coumaryl 7- hydroxyl salidroside, was assessed using MTT assay against MCF-7 and HT-29 carcinoma cells. Two known phenylpropanoid compounds were isolated from this species. Their structures were elucidated by spectroscopic data (using 1H-NMR and 13C-NMR) and compared with the previous literature. Both pure compounds in comparison with control group demonstrated significant antiproliferative activity against cancerous cells (P < 0.001). In our study, verbascoside and its derivative could inhibit proliferation of cancerous cells without any side effects on normal cells.